Possible explanation for limited reduction of pathogens on radish microgreens after spray application of chlorinated water during growth with disperse contamination spread of abiotic surrogate on leaves - Işık, Sefa; Aytemis, Zeynep; Çetin, Bülent; Topalcengiz, Zeynal (Wiley, 2022)
The purpose of this study was to determine the efficacy of spray application of chlorinated water before harvest on the population of Salmonella enterica Typhimurium and Escherichia coli O157:H7 on radish microgreens. The transfer of abiotic surrogate to radish microgreens was also evaluated to track possible pathogen contamination spread by inoculating seed and growth media. During growth, microgreens inoculated with strains of pathogens were sprayed with chlorinated water at three different concentrations (0.50, 1.00, and 2.00 +/- 0.05 ppm free chlorine). Spray application of chlorinated water was performed on microgreens once (day 9), twice (day 8 and 9), three (day 7, 8, and 9), and four times (day 6, 7, 8, and 9). Microgreens were harvested 12 hr after the last application of chlorinated water. Salmonella and E. coli O157:H7 populations were reduced with the increase in chlorine concentration. Chlorinated water reduced Salmonella and E. coli O157:H7 populations up to 1.1 log CFU/g (p < .05) and 0.9 log CFU/g (p > .05), respectively. Images taken under UV illumination provided the visualization of abiotic surrogate spread on cotyledon and upper hypocotyl (all edible parts) of radish microgreen plants regardless of seed or growth media inoculation. Scanning Electron Microscopy showed the presence of abiotic surrogate and generic E. coli on microgreen leaves. Spray application of chlorinated water during microgreen growth may help to reduce microbial load but cannot be used as the only control measure.
Keywords: Shelf-Life; Microbial-Population; Postharvest Quality; Food Safety; Wash; Salmonella